Oral Health Status and Attitude of Patients towards Dental Extraction in Karachi - Asma Dahar; Faisal Hameed; Tahira Assad; Hira Jahangir (ziauddin University, 2020)
Background: Oral health is considered the most important factor in determining general health of an individual, since it reflects the condition of the whole body. This study was outlined to demonstrate the oral health status and attitude of patients toward tooth extraction in case of non-affordability. Methods: A total of 350 dental patients who came to OPDs for dental extraction were included in this study. Dentist carrying out extraction were asked to fill a self-explanatory questionnaire having patient as the subject. Data tabulation and analysis was completed using SPSS software version 22. Odds ratios, Chi square test, p-value are used to determine oral health status and attitude of patients regarding extraction of teeth. Results: There were 193(55%) female and 157(45%) male patients in the study. Age of the respondents varied from 20 to 65 with a mean of 40.01±12.67. In addition, 202(57.7%) subjects were unemployed and 148(42.3%) were employed. In present study, teeth were found missing mainly in the age range 20-30. Among all teeth, First molar was the most commonly extracted tooth i.e. 109(31.1%). This indicated that patients wanted to save their teeth. They were willing to pay anything to save tooth in which 137(67.8%) were unemployed while 95 (64.1%) were employed. Conclusion: Oral health status of the patients who came to OPD for dental extraction was found poor 150(42.9%). Since, patients were suffering from dental caries and periodontal disease. As far as the attitude of patients is concerned regarding tooth extraction, more employed (45.3%) individuals were interested in saving their tooth than unemployed people.